In Situ Generation of Pd-Pt Core-Shell Nanoparticles on Reduced Graphene Oxide (Pd@Pt/rGO) Using Microwaves: Applications in Dehalogenation Reactions and Reduction of Olefins - Goswami, Anandarup; Rathi, Anuj K; Aparicio, Claudia; Tomanec, Ondrej; Petr, Martin; Pocklanova, Radka; Gawande, Manoj B; Varma, Rajender S; Zboril, Radek (ACS applied materials & interfaces, 2017)
Core-shell nanocatalysts are a distinctive class of nanomaterials with varied potential applications in view of their unique structure, composition-dependent physicochemical properties, and promising synergism among the individual components. A one-pot microwave (MW)-assisted approach is described to prepare the reduced graphene oxide (rGO)-supported Pd-Pt core-shell nanoparticles, (Pd@Pt/rGO); spherical core-shell nanomaterials (∼95 nm) with Pd core (∼80 nm) and 15 nm Pt shell were nicely distributed on the rGO matrix in view of the choice of reductant and reaction conditions. The well-characterized composite nanomaterials, endowed with synergism among its components and rGO support, served as catalysts in aromatic dehalogenation reactions and for the reduction of olefins with high yield (>98%), excellent selectivity (>98%) and recyclability (up to 5 times); both Pt/rGO and Pd/rGO and even their physical mixtures showed considerably lower conversions (20 and 57%) in dehalogenation of 3-bromoaniline. Similarly, in the reduction of styrene to ethylbenzene, Pd@Pt core-shell nanoparticles (without rGO support) possess considerably lower conversion (60%) compared to Pd@Pt/rGO. The mechanism of dehalogenation reactions with Pd@Pt/rGO catalyst is discussed with the explicit premise that rGO matrix facilitates the adsorption of the reducing agent, thus enhancing its local concentration and expediting the hydrazine decomposition rate. The versatility of the catalyst has been validated via diverse substrate scope for both reduction and dehalogenation reactions.
Keywords: Pd@Pt/rGO; reduction; olefins; dehalogenation; recyclable; core−shell nanocatalysts